Pemasaran Produk Ayam Pedaging di Kota Kendari Pada Masa Isu Pandemi Covid-19 - Surni Surni; Munirwan Zani; Syamsuddin Syamsuddin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
The Covid-19 pandemic in Indonesia is gradually becoming normal, evidenced by the government's loosening policy to carry out offline activities. Educational, social, and economic activities have been going well. This study aims to determine the efficiency of broiler marketing in Kendari City. The approach used in this research is quantitative. The research was carried out in June 2022 in five Kendari City consumer centers (markets: Baruga, Anduonohu, Mandonga Central, Kendari Lama City Central, and Lawata). The data used are primary data from interviews with respondents and statistical data obtained from the Central Statistics Agency in secondary data and supported by literature studies. The data analysis technique used descriptive analysis. The results showed that the business scale of broiler breeders in Kendari City started from 3,000 - 10,500 heads in one livestock period. Marketing of broilers in Kendari City is through two marketing channels, marketing channel I from small traders in the market to final consumers and marketing channel II from producers to wholesalers in the market to final consumers. The analysis results show that the marketing of broiler products in Kendari City is running efficiently, each of which is indicated by the value of FS = 91% in marketing channel I and FS value = 74% in marketing channel II. The total profit earned by traders in the marketing channel I am Rp. 1,800,870.83/month, which is smaller than the profit earned by traders in marketing channel II, which is Rp. 37,422,631,80/month. Consumer responses to the price level (Rp24,666.30/kg – Rp32,188.00/kg) broilers in the Kendari City market are cheap and satisfied with the frequency of consumer shopping once and every day for the last month.